2022
DOI: 10.1021/acsomega.2c03017
|View full text |Cite
|
Sign up to set email alerts
|

Coal Structure Characteristics in the Northern Qinshui Basin and Their Discrimination Method Based on the Particle Size of Drilling Cuttings

Abstract: Coal structure, including primary coal, cataclastic coal, granulated coal, and mylonitized coal, is one of the key factors controlling coal and gas outburst, and it also determines the efficiency of coalbed methane (CBM) extraction. Therefore, it is significant to identify the characteristics of coal structures and to predict them in advance. In this work, the spatial distribution, mechanical properties, and microscopic morphology of the four coal structures from the No. 3 coal seam of the Xinyuan Mine in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Since the number of broken blocks is difficult to count, a screening test is carried out. To realize the quantitative expression of the degree of coal and rock fragmentation, Mandelbrot [74] and Zhao et al [75] established a mass-frequency relationship model based on the screening method, as shown in equation ( 6):…”
Section: Mass-frequency Relationship Modelmentioning
confidence: 99%
“…Since the number of broken blocks is difficult to count, a screening test is carried out. To realize the quantitative expression of the degree of coal and rock fragmentation, Mandelbrot [74] and Zhao et al [75] established a mass-frequency relationship model based on the screening method, as shown in equation ( 6):…”
Section: Mass-frequency Relationship Modelmentioning
confidence: 99%
“…Lyu et al and Yuan et al believed that natural fractures provide a direct flow channel for CBM and coalbed water, and it can be concluded that the distribution of fracture systems in the reservoir scale can significantly control the hydraulic fractures. , The tectonics of the CBM reservoir is complex, and the coal cementation is poor in China, especially the high brittleness of high-rank coal, which is easy to produce coal fines during the process of drilling, fracturing, and production (Figure ). , The sources of coal fines can be divided into five types: (1) primary coal fines from coal seams; (2) tectonic processes; (3) mechanical interference, such as hydraulic erosion, shear, and wear of the coal surface caused fluid during drilling and hydraulic fracturing; (4) the elastic self-regulation effect of coal seams when the stress of the coal matrix changes; and (5) flushing with gas and liquid during reverse discharge and production. During fracturing fluid backflow, the generated coal fine particles will enter the wellbore with flowing water, thereby blocking the underground water pump . Additionally, coal fines may block or deposit coal seam cleats, pores, and cracks during migration, , reducing the permeability of propping fractures and leading to a significant decrease in gas productivity.…”
Section: Introductionmentioning
confidence: 99%